Differential tumor immune microenvironment coupled with tumor progression or tumor eradication in HPV-antigen expressing squamous cell carcinoma (SCC) models - Shivarudrappa, Arpitha H.; John, Jessy; Vashisht, Monika; Ge, Huaibin; Liu, Silvia; Chen, Jingxin; Siddoway, Karen; Dong, Rui; Chen, Zhangguo; Wang, Jing H. (Frontiers in Immunology, 2024)
Human papilloma virus (HPV) is an etiological factor of head and neck squamous cell carcinoma (HNSCC). To investigate the role of HPV antigen in anti-tumor immunity, we established mouse models by expressing HPV16 E6 and E7 in a SCC tumor cell line. We obtained two HPV antigen-expressing clones (C-225 and C-100) transplantable into C57BL/6 recipients. We found that C-225 elicited complete eradication in C57BL/6 mice (eradicated), whereas C-100 grew progressively (growing). We examined immune tumor microenvironment (TME) using flow cytometry and found that eradicated or growing tumors exhibited differential immune profiles that may influence the outcome of anti-tumor immunity. Surprisingly, the percentage of CD8 and CD4 tumor-infiltrating lymphocytes (TILs) was much higher in growing (C-100) than eradicated (C-225) tumor. However, the TILs upregulated PD-1 and LAG-3 more potently and exhibited impaired effector functions in growing tumor compared to their counterparts in eradicated tumor. C-225 TME is highly enriched with myeloid cells, especially polymorphonuclear (PMN) myeloid-derived suppressor cells (MDSC), whereas the percentage of M-MDSC and tumor-associated macrophages (TAMs) was much higher in C-100 TME, especially M2-TAMs (CD206+). The complete eradication of C-225 depended on CD8 T cells and elicited anti-tumor memory responses upon secondary tumor challenge. We employed DNA sequencing to identify differences in the T cell receptor of peripheral blood lymphocytes pre- and post-secondary tumor challenge. Lastly, C-225 and C-100 tumor lines harbored different somatic mutations. Overall, we uncovered differential immune TME that may underlie the divergent outcomes of anti-tumor immunity by establishing two SCC tumor lines, both of which express HPV16 E6 and E7 antigens. Our experimental models may provide a platform for pinpointing tumor-intrinsic versus host-intrinsic differences in orchestrating an immunosuppressive TME in HNSCCs and for identifying new targets that render tumor cells vulnerable to immune attack.